Determinants of functional income distribution: Theory and empirical evidence - Petra Dun̈haupt (International Labour Organization (ILO), 2013)
Since the 1980s, the share of wages in national income declined almost all over the world. This paper provides an overview of the evolution of labour's share in selected OECD countries. Several theoretical approaches explaining functional income distribution are summarised. In light of the different theoretical stances, this paper reviews the empirical literature on potential explanations for the prolonged fall. While heterodox economists regard neo-liberalism, financialisation and the shift in workers' bargaining power as the main determinants for the decline in labour's share, neoclassical economists relate the fall to skilled-biased technological change and globalisation. The paper also offers recommendation on how to stabilise labour's share.
Keywords: 330; income distribution; wages; labour market; economic theory; OECD countries